Sean Lester : the guardian of a small flickering light - Fosse, Marit; Fox, John (Hamilton Books, 2016)
Although he had left school aged fourteen, had no experience of foreign affairs and spoke only English, in 1929 Sean Lester became the Irish representative to the League of Nations in Geneva, eventually succeeding to the post of its third and last Secretary-General. In his dairies he witnessed many dark chapters of European history in the 1930s and 1940s.